Dissecting the human serum antibody response to secondary dengue virus infections. - Bhumi Patel; Patti Longo; Michael J Miley; Magelda Montoya; Eva Harris; Aravinda M de Silva (Public Library of Science (PLoS), 2017)
Dengue viruses (DENVs) are mosquito-borne flaviviruses and the causative agents of dengue fever and dengue hemorrhagic fever. As there are four serotypes of DENV (DENV1-4), people can be infected multiple times, each time with a new serotype. Primary infections stimulate antibodies that mainly neutralize the serotype of infection (type-specific), whereas secondary infections stimulate responses that cross-neutralize 2 or more serotypes. Previous studies have demonstrated that neutralizing antibodies induced by primary infections recognize tertiary and quaternary structure epitopes on the viral envelope (E) protein that are unique to each serotype. The goal of the current study was to determine the properties of neutralizing antibodies induced after secondary infection with a different (heterotypic) DENV serotypes. We evaluated whether polyclonal neutralizing antibody responses after secondary infections consist of distinct populations of type-specific antibodies to each serotype encountered or a new population of broadly cross-neutralizing antibodies. We observed two types of responses: in some individuals exposed to secondary infections, DENV neutralization was dominated by cross-reactive antibodies, whereas in other individuals both type-specific and cross-reactive antibodies contributed to neutralization. To better understand the origins of type-specific and cross-reactive neutralizing antibodies, we analyzed sera from individuals with well-documented sequential infections with two DENV serotypes only. These individuals had both type-specific and cross-reactive neutralizing antibodies to the 2 serotypes responsible for infection and only cross-reactive neutralizing antibodies to other serotypes. Collectively, the results demonstrate that the quality of neutralizing (and presumably protective) antibodies are different in individuals depending on the number of previous exposures to different DENV serotypes. We propose a model in which low affinity, cross-reactive antibody secreting B-cell clones induced by primary exposure evolve during each secondary infection to secrete higher affinity and more broadly neutralizing antibodies.